2009
DOI: 10.3904/kjim.2009.24.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Serum Ferritin is Associated with the Outcome of Patients with Newly Diagnosed Multiple Myeloma

Abstract: Background/AimsSerum ferritin is a marker of acute phase reactions and iron storage. In addition, hematologic malignancies are associated with elevated serum ferritin levels. Other studies have suggested that ferritin is a surrogate for advanced disease and has an impact on relapse, because elevated serum ferritin predicts overall survival (OS) and relapse-free survival following autologous stem cell transplantation for lymphomas.MethodsWe studied 89 consecutive patients with newly diagnosed multiple myeloma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…It has been accepted in some areas of medicine, including in the prediction of vascular diseases [12,13], and in the field of oncology, anticipating inferior survival in advanced cancers [14]. Likewise, serum ferritin, an acute phase reactant [15], is an indicator of iron overload after repetitive packed red cell transfusion [16] and a biomarker of poor prognosis in patients with several hematologic malignancies [17][18][19]. However, the prognostic implication of these inflammatory markers in patients with acute leukemia seems inappropriate because the treatment of acute leukemia consists of the administration of high-dose chemotherapy and, in selected patients, HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been accepted in some areas of medicine, including in the prediction of vascular diseases [12,13], and in the field of oncology, anticipating inferior survival in advanced cancers [14]. Likewise, serum ferritin, an acute phase reactant [15], is an indicator of iron overload after repetitive packed red cell transfusion [16] and a biomarker of poor prognosis in patients with several hematologic malignancies [17][18][19]. However, the prognostic implication of these inflammatory markers in patients with acute leukemia seems inappropriate because the treatment of acute leukemia consists of the administration of high-dose chemotherapy and, in selected patients, HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, elevated ferritin was correlated with poor survival and was an independent predictor of mortality in MM (p= 0.002). 4 They observed an association between increased ferritin level and advanced ISS stage. However, they did not report on other serum iron tests, possible mechanisms of elevated ferritin in MM patients and the association between serum iron parameters and type of myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased TS is not compatible with acute phase response. Additionally, serum iron level was frequently borderline high to increased in the IOP cohort which 4 studied the importance of serum ferritin in 89 patients with newly diagnosed MM. They observed that the overall survival in the elevated serum ferritin group was shorter than that in the normal serum ferritin group (p< 0.001) after a median follow-up of 25 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More modest elevations of ferritin levels of 300 ng/ mL and above have been associated with increased mortality in the setting of multiple myeloma [9] and childhood neuroblastoma [10]. In lung cancer patients ferritin values above 300 ng/mL were significant predictors of survival even adjustment for covariates such as performance status, age, sex, TNM stage, and histological tumor type [11].…”
Section: Discussionmentioning
confidence: 99%